2022
DOI: 10.21203/rs.3.rs-1928427/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence, trends, and factors associated with teen motherhood in Nigeria: An analysis of the 2008-2018 Nigeria Demographic and Health Surveys.

Abstract: Backgrounds: Teen pregnancy and childbearing are common in Nigeria, and understanding the complexities such as sociodemographic and economic factors including sexual and reproductive health knowledge and awareness among adolescents over time can trigger innovative approaches and interventions. This study intends to capture the patterns and associated factors of teen motherhood among sexually active adolescents (15-19 years) between 2008-2018.Methods: The study data was extracted from 2008, 2013, and 2018 Niger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The section reviews empirical studies from which hypotheses were developed and verified by study results. Kareem et al (2023) analyzed the situation of teenagers' motherhood in their article on Prevalence, Trends, and Factors Associated with Teen Motherhood in Nigeria. Through a desk review, data provided by Nigeria Demographic and Health Survey in 2008, 2013 and 2018 revealed that team mothers' phenomenon increased over 10 years by 50.9%, 52.4% and 55.2% and was find to be the major cause of death among teenagers.…”
Section: Empirical Review and Hypotheses Developmentmentioning
confidence: 99%
“…The section reviews empirical studies from which hypotheses were developed and verified by study results. Kareem et al (2023) analyzed the situation of teenagers' motherhood in their article on Prevalence, Trends, and Factors Associated with Teen Motherhood in Nigeria. Through a desk review, data provided by Nigeria Demographic and Health Survey in 2008, 2013 and 2018 revealed that team mothers' phenomenon increased over 10 years by 50.9%, 52.4% and 55.2% and was find to be the major cause of death among teenagers.…”
Section: Empirical Review and Hypotheses Developmentmentioning
confidence: 99%